Hyperacusis in patients with complex regional pain syndrome related dystonia. Issue 12 (30th April 2007) - de Klaver, M J M; van Rijn, M A; Marinus, J; Soede, W; de Laat, J A P M; van Hilten, J J
Abstract : Introduction: In complex regional pain syndrome type 1 (CRPS-1), patients may have manifestations of central involvement, including allodynia, hyperalgesia or dystonia. We noted that more severely affected patients may experience hyperacusis, which may also reflect central involvement. The aim of this study was to evaluate the occurrence and characteristics of hyperacusis in patients with CRPS related dystonia. Methods: The presence of hyperacusis, speech reception thresholds (SRT), pure-tone thresholds (PTT) and uncomfortable loudness (UCL) was evaluated in 40 patients with CRPS related dystonia. Results: PTT and SRT were normal for all patients. 15 patients (38%) reported hyperacusis and this was associated with allodynia/hyperalgesia and with more affected extremities. UCLs of patients with hyperacusis were significantly lower than UCLs of patients without hyperacusis. Conclusion: Hyperacusis is common among severely affected patients with CRPS related dystonia and may indicate that the disease spreads beyond those circuits related to sensory–motor processing of extremities.